RETRACTED: An Experimental Study of Picture Word Inductive Model to Foster Students’ Vocabulary in an Indonesian Junior Highschool Setting - Suraya Mukadar; Abd Rahman; Melani Putri Launuru (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
RETRACTED: The objective of the research is to know whether the application of Picture word inductive model improve students’ vocabulary at SMP Negeri 2 Jikumerasa. In this research, the researcher used quantitative research method with pre-Experimental design of the one group pretest and posttest. The sample of the research was 26 students learning at the seventh grade of SMP Negeri 2 Jikumerasa which consist of 7 male students and 19 female students. The data were collected by using 30 items of multiple choices test. The data obtained were analyzed by applying dependent t-test the formula. The result of the analysis show that the average score in posttest X2 = 1818 is greater than score of pretest X1 = 1449, calculation of t-test = 9.39 exceeds the t-table = 1.711 at significant level of = 0.05. Thus the alternative hypothesis (Hα) stating that the use of Picture word inductive model improve students English vocabulary is accepted while the null hypothesis (H0) which stated that the Picture Word Inductive Model could not improve students’ English vocabulary was rejected. The findings suggested that the model serves as an alternative to foster students’ English vocabulary in EFL classroom setting.